Religious Literature in Posthumous Inventories of the Small Town Burghers in Poland (Sixteenth–Eighteenth Centuries) - Justyniarska-Chojak, Katarzyna ca. 20./21. Jh. (Church history and religious culture, 2025)
The posthumous inventory, as an "official listing of things," assumed the preparation of a register of all movable and immovable property that the testator had at the time of death. Bartłomiej Groicki (ca. 1534-1605), a Polish expert in Magdeburg law, encouraged burghers to prepare such registers, because they made it possible to estimate the size of the property left to the heirs and to indicate the debts that burdened the inheritance. According to the law, the heirs assumed the obligation to repay all financial obligations. If the amount of the debt exceeded the value of the inherited property, the heirs could reject such an inheritance. In the posthumous inventories of Polish burghers, we encounter various categories of movable property, including books. It is worth noting, however, that there are not many such lists in the surviving city books. However, the analysis of titles appearing in the town registers allows us to state that most of the posthumous books recorded in the inventories were works on religious themes. The source basis for the article will be handwritten posthumous inventories from small towns in the Małopolska region in Poland and printed registers of Poznań residents. Its aim will be to show examples of religious writing appearing in the registers and to answer the question of what works reached people living in the towns of Małopolska. The presence of this type of writing in the registers may indicate the spiritual needs of the townspeople and the changing forms of devotion over time.